2012
DOI: 10.1007/s12155-012-9193-3
|View full text |Cite
|
Sign up to set email alerts
|

An Index of Competition Reduces Statistical Variability and Improves Comparisons between Genotypes of Miscanthus

Abstract: It is important for breeders and producers to be aware of competition effects for variety trials. We aimed at developing an index of competition to reduce statistical variability in field trials and improve comparisons between genotypes of Miscanthus. Twenty-one clones belonging to four species of Miscanthus (M. x giganteus, M. floridulus, M. sinensis, and M. sacchariflorus) planted at the same density were compared at two harvest dates during the second and third crop years. Aboveground volume was shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…The aboveground plant volume index (expressed in cm 3 ) was calculated as a function of the canopy height, stem number per plant, and stem diameter according to Zub et al (2012a):…”
Section: Calculation Of the Aboveground Plant Volume Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…The aboveground plant volume index (expressed in cm 3 ) was calculated as a function of the canopy height, stem number per plant, and stem diameter according to Zub et al (2012a):…”
Section: Calculation Of the Aboveground Plant Volume Indexmentioning
confidence: 99%
“…In addition, Zub et al (2012a) reported that the aboveground plant volume index of Miscanthus was a reliable predictor of the biomass produced in the second and third years. Our results confirmed these findings over a longer time period (from the second to the sixth year).…”
Section: Reliable Predictors Of Biomass Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zub et al [150] found that the aboveground volume including the stem number, the stem diameter and the plant height was a good predictor of plant biomass yield. Within genotypes, strong positive relationships were observed between biomass yield and the aboveground volume regardless of crop year (equal to 0.70 and 0.82 for autumn and winter harvests during the second year, respectively).…”
Section: © Inra -E Rosiaumentioning
confidence: 99%
“…In Miscanthus, the residual term was high during the second and third years of the crop (Zub et al [150]) and could hamper inter-genotypic comparisons for traits such as aboveground biomass yield or related traits. Without more plots or samples (it is indeed important for the breeder and the producer to save place and cost), one way for reducing the residual term is to take into account intra-genotypic competition effect in the statistical model [150]. As it implies observations at the plant level, intragenotypic effect assessment requires easyto-measure variables, such as the stand volume as a predictor of the aboveground biomass [150,151].…”
Section: © Inra -E Rosiaumentioning
confidence: 99%